A C-type lectin containing two carbohydrate recognition domains participates in the antibacterial response by regulating the JNK pathway and promoting phagocytosis. Issue 127 (August 2022) - Chen, Hong-Ye; Li, Wen-Ya; Wang, Jie; Bo, Gong-Wen; Yang, Gui-Wen; Yang, Hui-Ting
Abstract: C-type lectins (CTLs) are important immune-related molecules in crustaceans. However, the immunologic mechanism by which CTLs eliminate invading pathogens is still unclear. In this study, we studied the antimicrobial mechanism of a CTL containing two carbohydrate recognition domains (DClec). After Aeromonas hydrophila challenge, several antimicrobial peptides (ALF1, ALF4, ALF5 and lys-i2) were upregulated. The transcript levels of ALF1, ALF4 and ALF5 were downregulated after A. hydrophila challenge in groups with DClec interference or inhibition compared with the control group. Similar results were obtained after c -Jun N-terminal kinase (JNK) interference. This finding indicates that DClec might regulate the JNK signalling pathway and subsequently adjust antimicrobial peptide (AMP) expression. Additionally, we found that DClec was secreted into the hemolymph. Recombinant protein DClec (rDClec) agglutinated gram-positive or gram-negative bacteria. Both rDClec and the native DClec in hemolymph bound to different bacteria. In this process, Ca 2+ promoted the rDClec bacterial binding ability. After DClec interference, the phagocytosis ability of hemocytes was lower than that of the control group. Therefore, DClec can facilitate bacterial elimination by promoting AMPs expression and hemocyte phagocytosis. Highlights: DClec regulates the JNK pathway and influences antimicrobial peptides expression. DClec could be secreted into hemolymph and promote agglutinate bacteria. DClec could facilitate phagocytosis ability of hemocytes.